The Role of the Church in Reintegration of Street Children into Their Families in Lusaka District (British Journal of Multidisciplinary and Advanced Studies, 2025)
The purpose of the study was to analyze the role of the church in the reintegration process and to come up with new strategies for increasing the effectiveness of these rehabilitation activities. The study objectives were to establish the type of support churches provide to the families with children on the street in Lusaka district and to assess the church-led initiatives that foster positive parent-child relationships after integration of street children in Lusaka district. A total sample of five families, 15 family members and four counsellors totaling to 19 participants made the total sample of the study. Interviews were conducted with parents and their children while a focus group discussion was conducted in this study at the sampled church grounds. Data was analyzed thematically by sorting similar responses and created themes under which the findings were presented. The study found that that under family talk on child care, it was the responsibility of the family to initiate family integration was initiated by the willingness of the family and the child at the same time. With regards to child safety and future consequences, the church had a responsibility to ensure that the family provided safety guarantees for the child before the child could be talked to by the church counsellors. On food provision to broken families, the church provided start up packs for families which were struggling to keep their children at home. the financial provision for family sustainability was available to the parents whose children were integrated into the family and the parents were helped financially with capital for business and employment as maids or guards to help them earn a living. It can be concluded that the church and parents played a crucial role in ensuring that there was effective and peaceful integration of children into the main family. The study recommended that Churches should come to the aid of the parents and homes where children have left for the streets so that family integration is supported. This will enable members of the church to feel safe to belong to the church since there will be enough help